Lessons learned in the challenging case of evolving compartment syndrome with atypical presentation - Ng, Jessica (BMJ Case Rep, 2019)
We present the rare case of a non-painful compartment syndrome of the forearm in a 35-year old man with a history of intravenous drug abuse, and lessons learned which would have enabled earlier consideration of this limb threatening condition and earlier therapeutic intervention. On initial assessment in the emergency department, the patient was drowsy, tachycardic and pyrexic. There was no obvious pain outwith expectation, and his forearm was erythematous and swollen. Due to the constellation of symptoms and signs, he was presumed to be septic from a forearm cellulitis and was thus treated for sepsis with intravenous antibiotics under the care of the medical team. As his arm swelling continued, he was then thought to possibly have a vascular issue and was given a therapeutic dose of low molecular weight heparin. He was otherwise pain free throughout and had no evidence of neurological compromise. A subsequent orthopaedic review raised the concern of compartment syndrome, and this, alongside a clinically evolving picture, resulted in a diagnosis of developing compartment syndrome being made. The patient underwent subsequent surgical management with dual incision fasciotomies and definitive wound management with split skin graft under the care of plastic surgery. This is a rare presentation of a masked developing compartment syndrome. This case highlights the importance of considering atypical presentations of compartment syndrome in high risk patients, and the importance of early specialist orthopaedic referral, particularly in those who do not present with typical features in their history and examination. We summarise the lessons learned in this case which would have enabled earlier identification of this limb-threatening diagnosis and could have improved further definitive outcome.